2011
DOI: 10.1007/s13238-011-1119-x
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide RNAi screen identifies genes regulating the formation of P bodies in C. elegans and their functions in NMD and RNAi

Abstract: Cytoplasmic processing bodies, termed P bodies, are involved in diverse post-transcriptional processes including mRNA decay, nonsense-mediated RNA decay (NMD), RNAi, miRNA-mediated translational repression and storage of translationally silenced mRNAs. Regulation of the formation of P bodies in the context of multicellular organisms is poorly understood. Here we describe a systematic RNAi screen in C. elegans that identified 224 genes with diverse cellular functions whose inactivations result in a dramatic inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
2
30
1
Order By: Relevance
“…However, another study reported that deletion of the NLS completely blocks FUS toxicity, as did the addition of a NES [211]. Blocking the RNA binding capacity of FUS also abolishes FUS toxicity in yeast [178] and ameliorates mutant FUS toxicity in Drosophila [42] (Supplementary Table). Although further work is needed to reveal to which extent mislocalization of mutant FUS contributes to disease, recent studies show that mutant FUS triggers stress granule formation and loss of nuclear GEMs, as will be discussed in more detail in the next section.…”
Section: Novel Insights Into the Molecular Makeup And Formation Of Cementioning
confidence: 99%
“…However, another study reported that deletion of the NLS completely blocks FUS toxicity, as did the addition of a NES [211]. Blocking the RNA binding capacity of FUS also abolishes FUS toxicity in yeast [178] and ameliorates mutant FUS toxicity in Drosophila [42] (Supplementary Table). Although further work is needed to reveal to which extent mislocalization of mutant FUS contributes to disease, recent studies show that mutant FUS triggers stress granule formation and loss of nuclear GEMs, as will be discussed in more detail in the next section.…”
Section: Novel Insights Into the Molecular Makeup And Formation Of Cementioning
confidence: 99%
“…In developing C. elegans embryos, LSM-1 is present only in somatic blastomeres, whereas DCAP-2 localizes in P granules in germline blastomeres (Lall et al 2005). Another PB component, the decapping enzyme DCAP-1, localizes in granules that are only weakly reduced upon lsm-1 RNAi inactivation (Sun et al 2011). Moreover, in adult animals, although DCAP-1-positive granules have been described to increase in size with age (Sun et al 2011), we did not observe this effect in LSM-1::GFP worms (not shown).…”
Section: Cytoplasmic Lsm Granules: P-bodies or Stress Granules?mentioning
confidence: 99%
“…P granules are the most characterized RNA granules in worms and are highly involved in cellular development (Updike and Strome, 2010). However, human proteins found in P bodies and stress granules, such as TIA1, the decapping enzymes and polyA binding proteins, have C. elegans ortholog and their role seem conserved regarding RNA granules (Jud et al, 2008;Sun et al, 2011). An active area of research concerns whether mutant TDP-43 and/or FUS proteins interfere with stress granule homeostasis.…”
Section: Stress Response and Age-dependent Neurodegeneration In C Elmentioning
confidence: 99%
“…In a transgenic model of FUS, wild type and mutant FUS were shown to colocalize to stress granules after a heat shock but only the recruitment of mutant FUS to the stress granules caused persistent motility defects in the worms (Murakami et al, 2012). Most work done in C. elegans to study stress granules have used thermal stress as an inducer of the granule (Sun et al, 2011). In cells, formation of granules containing FUS is also initiated by other environmental stresses such as osmotic stress (Baron et al, 2013) and oxidative stress (Vance et al, 2013), thus the effect of these other stresses would be interesting to evaluate.…”
Section: Stress Response and Age-dependent Neurodegeneration In C Elmentioning
confidence: 99%